2019
DOI: 10.1002/1348-9585.12085
|View full text |Cite
|
Sign up to set email alerts
|

The effects of training managers on management competencies to improve their management practices and work engagement of their subordinates: A single group pre- and post-test study

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited and is not used for commercial purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…Previous studies showed that senior executives of public hospitals in China tended to increase their participation in informal management-related training after taking up a management position [ 24 , 25 ], only to find it difficult to commit sufficient time for study and learning. Evidence from different industries and healthcare systems in the past two decades confirms that management competence can be acquired and improved through targeted training programs and continuous professional development [ 40 – 42 ]. However, universities should tailor their education strategies towards meeting developmental needs within work environments through partnerships with health care organisations [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that senior executives of public hospitals in China tended to increase their participation in informal management-related training after taking up a management position [ 24 , 25 ], only to find it difficult to commit sufficient time for study and learning. Evidence from different industries and healthcare systems in the past two decades confirms that management competence can be acquired and improved through targeted training programs and continuous professional development [ 40 – 42 ]. However, universities should tailor their education strategies towards meeting developmental needs within work environments through partnerships with health care organisations [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies conducted in different industries and healthcare contexts over the past 20 years suggest that management competence can be acquired and improved through targeted training programs and continuous professional development [8][9][10][11]. For example, a recent study using the UK Health and Safety Executive Management Competency Framework to train financial managers in Japan demonstrated the effectiveness of training programs in developing management competence and facilitating better work engagement between managers and subordinates [10].…”
Section: Overall Health Management Workforce Developmentmentioning
confidence: 99%
“…Studies conducted in different industries and healthcare contexts over the past 20 years suggest that management competence can be acquired and improved through targeted training programs and continuous professional development [ 8 , 9 , 10 , 11 ]. For example, a recent study using the UK Health and Safety Executive Management Competency Framework to train financial managers in Japan demonstrated the effectiveness of training programs in developing management competence and facilitating better work engagement between managers and subordinates [ 10 ]. A recent nursing internship program implemented at the Centre for Addiction and Mental Health (CAMH) in Toronto, Canada confirmed the success of professional development and mentoring in developing nursing leaders’ competency guided by the Canadian College of Health Leaders Framework (LEADs) (2013) [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have shown that work engagement as a mediator in connection management sources in reach employee performance (Tensay & Singh, 2020). Work engagement could be through training programs created by managers to increase competence and facilitation work engagement (Adachi et al, 2020). According to (Stirpe et al, 2022) role HR practices affect satisfaction and work engagement, also stated by research (Moore et al, 2020) that employee management influences satisfaction and engagement.…”
Section: Introductionmentioning
confidence: 99%